The role of educational curricula in developing some life skills in the era of globalization from the point of view of students of physical education faculties - سلمان ريم (Latakia University Journal -Medical Sciences Series, 2022)
The study aimed to identify the role of educational curricula in developing some life skills in light of the era of globalization from the point of view of students of physical education faculties, where the questionnaire was used as a tool for data collection. Communication and communication skills, social skills and teamwork, thinking and discovery skills). The questionnaire was applied to a sample of (150) male and female students from the faculties of physical education at Tishreen University and Hama University from the level of the third and fourth academic year, who were chosen randomly. To analyze the results, the t-test was used to test the differences between the averages of the independent samples. The results showed that the educational curricula in the faculties of physical education in Syria work on developing the life skills required by the era of globalization.